2016
DOI: 10.1016/j.expneurol.2016.02.023
|View full text |Cite
|
Sign up to set email alerts
|

The role of growth factors as a therapeutic approach to demyelinating disease

Abstract: A variety of growth factors are being explored as therapeutic agents relevant to the axonal and oligodendroglial deficits that occur as a result of demyelinating lesions. This review focuses on five such proteins that are present in the lesion site and impact oligodendrocyte regeneration. It then presents approaches that are being exploited to manipulate the lesion environment affiliated with multiple neurodegenerative diseases and suggests that the utility of these approaches can extend to demyelination. Chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 198 publications
0
39
0
Order By: Relevance
“…Systemic FAK inhibition in β-gal CNTF reporter heterozygous mice, had increased CNTF expression in areas neighboring the SVZ, including striatum and the white matter of the corpus callosum, and overlying cortex. This may be relevant to rescuing striatal neurons in Huntington's disease and oligodendrocytes in multiple sclerosis, respectively, given CNTF's trophic effects in animal models (Huang & Dreyfus, 2016;Ramaswamy & Kordower, 2012). Our data suggest that promoting neurogenesis requires increased CNTF without concomitant increases in LIF and/or IL-6, which are known to reduce neuroblast formation by promoting stem cell selfrenewal (Bauer & Patterson, 2006;Bowen et al, 2011;Covey et al, 2011;Gregg & Weiss, 2005;Pitman et al, 2004;Shimazaki et al, 2001).…”
Section: Fak-jnk Pathway Inhibition Uniquely Increases Cntf Expressmentioning
confidence: 71%
See 1 more Smart Citation
“…Systemic FAK inhibition in β-gal CNTF reporter heterozygous mice, had increased CNTF expression in areas neighboring the SVZ, including striatum and the white matter of the corpus callosum, and overlying cortex. This may be relevant to rescuing striatal neurons in Huntington's disease and oligodendrocytes in multiple sclerosis, respectively, given CNTF's trophic effects in animal models (Huang & Dreyfus, 2016;Ramaswamy & Kordower, 2012). Our data suggest that promoting neurogenesis requires increased CNTF without concomitant increases in LIF and/or IL-6, which are known to reduce neuroblast formation by promoting stem cell selfrenewal (Bauer & Patterson, 2006;Bowen et al, 2011;Covey et al, 2011;Gregg & Weiss, 2005;Pitman et al, 2004;Shimazaki et al, 2001).…”
Section: Fak-jnk Pathway Inhibition Uniquely Increases Cntf Expressmentioning
confidence: 71%
“…This may be relevant to rescuing striatal neurons in Huntington’s disease and oligodendrocytes in multiple sclerosis, respectively, given CNTF’s trophic effects in animal models (Huang and Dreyfus 2016; Ramaswamy and Kordower 2012). …”
Section: Discussionmentioning
confidence: 99%
“…FGF‐2 is a mediator of adult neurogenesis and described in the literature to be involved in the recruitment of OPCs (Watts et al, ). Recent research showed that FGF‐2 is highly expressed by active astrocytes in the subventricular zone in the adult brain, enhances the recruitment of progenitor cells, and therefore facilitates myelin repair (Azin, Mirnajafi‐Zadeh, & Javan, ; Huang & Dreyfus, ). In experimental demyelination, FGF‐2 mRNA levels peaked at the initial stage of remyelination supporting a remyelination‐enhancing role (Messersmith, Murtie, Le, Frost, & Armstrong, ).…”
Section: Discussionmentioning
confidence: 99%
“…The improvement observed in PDGF for both overweight and normal weight participants represents another beneficial effect of exercise training; as it has been shown that a higher level of PDGF can reduce clinical consequences of damage in multiple sclerosis and increase progenitors and reversal of cell death in CNS (Huang and Dreyfus, 2016). Exercise research on PDGF is limited, Czarkowska-Paczek et al, found that endurance training enhanced PDGF expression in rat skeletal muscle (Czarkowska-Paczek et al, 2010); however, Trenerry et al, reported although acute exercise increased PDGF expression, there was no change after 12 weeks of resistance exercise (Trenerry et al, 2011).…”
Section: Exercise-related Neurotrophic Factors Modulationmentioning
confidence: 99%
“…Some of the evaluated markers in the current study are secreted from a variety of tissues. For example, BDNF is released from the brain, muscle, and some immune cells (Huang et al, 2014;Huang and Dreyfus, 2016;Onuoha et al, 1998).…”
Section: Limitation 14mentioning
confidence: 99%